THE EFFECT OF CORPORATE GOVERNANCE ON FINANCIAL STABILITY SHARIA BANK IN INDONESIA - Joko Susanto; Sri Walyoto (Journal of Management and Islamic Finance, 2023)
This study aims to determine the effect of corporate governance on the financial stability of Islamic banks in Indonesia as measured using the z-score. The characteristics of the board of commissioners are proxied by the variable size of the board of commissioners, independent board of commissioners, board of commissioners meetings, and educational background of the board of commissioners. The study used panel data with a sample of Islamic commercial banks in Indonesia from 2015 to 2016 with a total sample of 78 data. The data analysis technique used multiple linear regression with the fixed effect model and the classical assumption test for the suitability of the regression model. The test results show that the variable size of the board of commissioners, independent board of commissioners, and educational background of the board of commissioners has no effect on the soundness of Islamic banks. Meanwhile, the board of commissioners meeting variable has a positive effect on the soundness level of Islamic banks. The control variables for bank size and NPF have no effect on bank soundness.